The art brut by Jean Dubuffet (Palíndromo, 2019)
This study has as a reflection around the ideals defended by the French artist Jean Dubuffet for the conception of the terminology art brut. During the 1940s, the artist expressively demonstrated his positions on art, culture and politics, as regards the formation of society and social issues. Such arguments make it pos-sible to understand certain concepts and trends approached by Dubuffet in his interpretations of art brut productions. Despite its apparent contradiction and utopian yearnings, Dubuffet valued art brut and fostered the emergence of new dialogues and perspectives on the arts.
Keywords: art brut; art and insanity; Jean Dubuffet